Use of borosilicate glass powder in cementitious materials: Pozzolanic reactivity and neutron shielding properties. (September 2020) - Moradllo, Mehdi Khanzadeh; Chung, Chul-Woo; Keys, Mitchell H.; Choudhary, Antara; Reese, Steven R.; Weiss, W. Jason
Abstract: This work evaluates both the pozzolanic reactivity and neutron shielding properties of cementitious paste and mortar mixtures containing varying amount of borosilicate glass powder. The experimental results indicate that the use of borosilicate glass powder results in a greater heat of hydration than that expected for cement paste alone at early ages (despite the fact that the cumulative heat release was reduced as the replacement of borosilicate glass powder increased). The maximum pozzolanic reactivity of borosilicate glass powder was estimated to be 55%, which was greater than a typical class F fly ash (≈30%). Borosilicate glass powder resulted in a 8% increase in the 28 d compressive strength of mortar for the replacement levels of up to 25% by mass. The neutron attenuation coefficient of mortar increased (10–40%) as the amount of borosilicate glass powder increased; however, it appears to plateau when the cement replacement ratio was higher than 25%. This plateau appears to be the result of competing effects (i.e., the addition of borosilicate glass powder continuously increases the attenuation coefficient while the reduction in hydration products reduces the attenuation coefficient). Based on initial testing, considering compressive strength and neutron shielding properties, the use of borosilicate glass powder in cementitious materials shows the best results when the replacement level is between 20 and 25% by mass of cementitious materials and when the cementitious system is properly cured. A simplified model was introduced to determine the required thickness of mortar with different mixture proportions for neutron shielding.